A multi-featured model for estimation of thermodynamic properties, adiabatic flame temperature and equilibrium combustion products of fuels, fuel blends, surrogates and fuel additives - Kayadelen, Hasan Kayhan (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
This study introduces a new multi-featured equilibrium combustion model for fuels, fuel blends and surrogates which estimates mole fractions, adiabatic flame temperature and thermodynamic properties of the equilibrium combustion products. The model enables simultaneous consideration of unlimited number of C alpha H beta O gamma N delta type fuels of different ratios and also enables any C alpha H beta O gamma N delta, type fuel additive, Argon, H2O, CO, CO2, N-2, and O-2 to be considered among the reactants. Equilibrium mole fractions and adiabatic flame temperature are not only necessary for estimating thermodynamic properties of exhaust gases but also provide key data to obtain the non-equilibrium concentrations. As for thermodynamic properties, precise calculation is necessary for accurate performance estimations of internal combustion engines. Meeting these fundamental needs and providing combustion analysis of numerous fuel blends of various mixing ratios, this new model can be a recourse tool for researchers working on fuels, surrogates, emissions and internal combustion engine modelling. Simulations of any combustion process including existence of exhaust gas recirculation, supplementary firing, steam injection, argon dilution, water injection, fuel emulsification and reheat process in gas turbines can easily be conducted by integrating this validated model into thermodynamic cycle models. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Combustion; Chemical equilibrium; Fuel blends; Emulsions; Steam injection; Argon dilution; EXHAUST-GAS RECIRCULATION; DUTY DIESEL-ENGINE; ARGON INERT-GAS; TURBINE PERFORMANCE; SI ENGINE; EMISSION CHARACTERISTICS; THERMAL EFFICIENCY; POWER-GENERATION; SINGLE CYLINDER; Thermodynamics; Energy & Fuels